The Role of Viral Proteins in the Regulation of Exosomes Biogenesis - Jia, Xiaonan; Yin, Yiqian; Chen, Yiwen; Mao, Lingxiang (Frontiers in Cellular and Infection Microbiology, 2021)
Exosomes are membrane-bound vesicles of endocytic origin, secreted into the extracellular milieu, in which various biological components such as proteins, nucleic acids, and lipids reside. A variety of external stimuli can regulate the formation and secretion of exosomes, including viruses. Viruses have evolved clever strategies to establish effective infections by employing exosomes to cloak their viral genomes and gain entry into uninfected cells. While most recent exosomal studies have focused on clarifying the effect of these bioactive vesicles on viral infection, the mechanisms by which the virus regulates exosomes are still unclear and deserve further attention. This article is devoted to studying how viral components regulate exosomes biogenesis, composition, and secretion.